Pemanfaatan Media Audiovisual Untuk Meningkatkan Minat Baca Siswa Dalam Pembelajaran Ekosistem di SD Negeri Gudang Garam Distrik Skanto Kabupaten Keerom - Maya Pujowati; Tri Suwarningsih; Etty Octaviani Manalu (Jayapangus Press, 2026)
This study aims to improve the reading interest of fourth-grade students at SD Negeri Gudang Garam, Skanto District, Keerom Regency through the use of audiovisual media in ecosystem and environmental learning. The research employed Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The subjects were 24 fourth-grade students, comprising 13 boys and 11 girls. Data were collected using observation sheets and reading interest questionnaires, then analyzed descriptively and qualitatively. The findings revealed a significant increase in students’ reading interest from 68.5% in cycle I to 86.25% in cycle II, with an overall improvement of 17.75%. The enhancement was evident in students’ interest in reading, focus, reading frequency, and active participation in literacy activities. Audiovisual media successfully created engaging learning environments, enhanced student concentration, and fostered intrinsic motivation to read. Therefore, the use of audiovisual media is effective in improving students’ reading interest and cultivating a culture of literacy in elementary schools, especially in remote areas with limited learning resources.